Incidental Findings of Computed Tomography Angiography in Patients Suspected to Pulmonary Embolism; a Brief Report - Korkut, Mustafa; bedel, cihan; Erman, Kürsat; Yüksel, Serkan (Archives of Academic Emergency Medicine, 2019)
Introduction: Computed tomography pulmonary angiography (CTPA) scans are increasingly used in emergency department (ED). Therefore, the observation of incidental findings (IFs) has also increased. This study aimed to evaluate the frequency of IFs in patients who underwent CTPA. Methods: All consecutive patients that underwent CTPA scanning for pulmonary embolism (PE) rule out between January 2017 and June 2018 were analysed. Incidental findings were divided into and reported in three categories: group 1 potentially life-threatening, group 2 required follow up, and group 3 with limited clinical significance. Results: 151 cases with the mean age of 61.2 ± 17.6 years were studied (54.3% female). PE was documented in 77 cases (50.9%). 448 IFs were detected (3 IFs were found per patient). 60 (13.3%) IFs were classified as group 1, 180 (40.1%) as group 2, and 208 (46.6%) as group 3. Cardiomegaly was the most frequent finding in group 1 (n=32), followed by aortic aneurysm (n=13). In group 2, pleural effusion (n=58) and pneumonia (n=36) were the most frequent incidental findings. Lung structure changes (n=92) and thoracic bone related findings (n=43) were the most common IFs observed in group 3. Conclusion: IFs were detected in the majority of patients that underwent CTPA. Most of these findings do not require follow-up or treatment. However, more than 50% of cases may require further diagnostic evaluation (40.1%) or immediate treatment (13.3%).